Monitoring treatment response to tafamidis by serial native T1 and extracellular volume in transthyretin amyloid cardiomyopathy. (27th November 2018) - Shintani, Yasuhiro; Okada, Atsushi; Morita, Yoshiaki; Hamatani, Yasuhiro; Amano, Masashi; Takahama, Hiroyuki; Amaki, Makoto; Hasegawa, Takuya; Ohta‐Ogo, Keiko; Kanzaki, Hideaki; Ishibashi‐Ueda, Hatsue; Yasuda, Satoshi; et al.
Abstract: Tafamidis meglumine, a transthyretin (TTR) stabilizer, is effective in delaying the progression of neuropathy in TTR amyloidosis with Val30Met mutations. However, its efficacy in TTR amyloid cardiomyopathy is not fully elucidated. Herein, we report a 73‐year‐old Japanese man with a diagnosis of TTR amyloid cardiomyopathy with Val30Met mutation treated with tafamidis. To evaluate treatment response, cardiac magnetic resonance imaging was performed before and after 12 months of tafamidis treatment. Native T1, extracellular volume, and left ventricular mass showed no obvious worsening, and findings of other diagnostic studies also supported the efficacy of tafamidis to delay the progression of amyloid cardiomyopathy. Our case suggests that serial native T1 and extracellular volume may be novel non‐invasive imaging methods to monitor the treatment response to TTR stabilizers in cardiac amyloidosis and also that tafamidis may be effective in suppressing cardiac progression in TTR amyloid cardiomyopathy with Val30Met mutation.